An investigation on the aggregate-shape embedded piezoelectric sensor for civil infrastructure health monitoring. (30th January 2017) - Song, Shanglin; Hou, Yue; Guo, Meng; Wang, Linbing; Tong, Xinlong; Wu, Jiangfeng
Highlights: A new piezoelectric sensor for infrastructure health monitoring is designed. 3D printing technique is used for sensor packaging. Sensor is designed in aggregate shape. Abstract: In this paper, a new type of aggregate-shape embedded piezoelectric sensor for health monitoring of civil infrastructures was developed. The sensor was designed by using piezoelectric ceramic chip as the functional phase, and a new composite material as packaging phase. 3D printing technology was also used for packaging system design and sensor fabrication. The frequency independence, linearity, sensitivity, response rate, and service performance of the sensor were tested by frequency scanning and amplitude scanning. Experimental results show that within the vibration frequency range of common civil engineering structures, the new aggregate-shape embedded piezoelectric sensor has good mechanical and workability properties. Test results also show that the new embedded sensors have very good mechanical-electrical coupling performance, which builds a solid foundation for further application in the civil engineering infrastructures.